2022
DOI: 10.1002/jobm.202200448
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of poly(3‐hydroxybutyrate‐co‐3‐hydroxvalerate) from volatile fatty acids by Cupriavidus necator

Abstract: A promising strategy to alleviate the plastic pollution from traditional petroleum‐based plastics is the application of biodegradable plastics, in which polyhydroxyalkanoates (PHAs) have received increasing interest owing to their considerable biodegradability. In the PHAs family, poly(3‐hydroxybutyrate‐co‐3‐hydroxvalerate) (PHBV) has better mechanical properties, which possesses broader application prospects. With this purpose, the present study adopted Cupriavidus necator to synthesize PHBV utilizing volatil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…While butyrate‐dominant VFA streams showed high potential on the biosynthesis of biodegradable polymers. Specifically, butyrate could obtain the highest maximum dry cell weight of 1.53 ± 0.06 g/L and polyhydroxyalkanoates (PHA) production of 1.04 ± 0.04 g/L [ 49 ]. The current study showed that adding a methanogenic inhibitor (BES) a is undoubtedly the most efficient method to promote VFA production on a laboratory scale.…”
Section: Discussionmentioning
confidence: 99%
“…While butyrate‐dominant VFA streams showed high potential on the biosynthesis of biodegradable polymers. Specifically, butyrate could obtain the highest maximum dry cell weight of 1.53 ± 0.06 g/L and polyhydroxyalkanoates (PHA) production of 1.04 ± 0.04 g/L [ 49 ]. The current study showed that adding a methanogenic inhibitor (BES) a is undoubtedly the most efficient method to promote VFA production on a laboratory scale.…”
Section: Discussionmentioning
confidence: 99%
“…Among the VFAs studied, valeric acid induced the highest accumulation of 3-hydroxyvalerate units. Cai et al have demonstrated in particular that even-carbon VFAs (acetate and butyrate) synthesized only poly(3-hydroxybutyrate) (PHB), while the addition of odd-carbon VFAs (propionate and valerate) resulted in PHBV production [5]. Tian et al also have mentioned that Photobacterium sp.…”
Section: Introductionmentioning
confidence: 99%
“…Proc. 2023, 56, 73 2 of 8 valerate) resulted in PHBV production [5]. Tian et al also have mentioned that Photobacterium sp.…”
Section: Introductionmentioning
confidence: 99%